Autogestão e economia solidária: limites e possibilidades - Sguarezi, Sandro Benedito (2011)
The socio-economic transformations of recent decades have brought consequences to the work world, influencing the direction of Brazil significantly. The State of Mato Grosso, was not immune to the impact of these transformations. The choice of current economic development model and the process of colonization promoted one of the most perverse concentration of income and land in the country. In addition, the State accumulated social, economic, cultural and environmental liabilities. In response to these problems solidarity economy came up based on self-management as an alternative to economic democratization. It has noticed that the social movements, through the social economy, are protagonists of a real and silent social transformation, paradigmatic and pragmatic. Silent because it is a transformation without guns, without violence, without exclusion. Paradigmatic because it demands from workers the transcendence from hetero-management to self-management and because it poses the challenge of democracy as a way of life. Pragmatic because it requires the advance of both internal and external organizational skills in every development creating strategic networks that enable the consolidation of this initiative. The research pursued the objective of identifying the limits and possibilities of self-management in solidarity economic enterprises (SEEs) in the state of Mato Grosso. The methodological approach was outlined by qualitative research because we understand that reality is socially constructed by the understandings that guide the way we investigate and it allows us to present the transcript of subjectivity in the process of knowledge construction. The main tools used were a literature review, unstructured interviews and participant observation at events and through on-site technical visits to enterprises. To broaden the understanding of the phenomenon, 30 interviews were conducted with representatives of the three segments that work in the field of social economy: Federal Government, Support and Development Entities (SDE) and Solidarity Economic Enterprises (SEEs). Based on these results we selected two reference projects of self-management for participative observation, one in the capital city and the other in the interior of the state. The analysis was organized on the basis of labor relations within the enterprise and the participation of the partners in decision-making process in these enterprises based on 14 indicators of self-management. The study results show the complexity involved in a polysemic concepts of solidarity economy and self-management and showed explicitly not only the differences and paradoxes on this phenomenon, but also indicate what the limits and possibilities of self-management for the construction of the solidarity economy. Among the limits we can highlight the lack of training, lack of self-management culture, lack of credit and the absence of a regulatory framework. It was also noted that the relations of self-management is limited to the internal relations of solidarity economic enterprises even though they relate with other social movements. Among the possibilities of self-management and solidarity economy, the rescue of self-esteem and dignity of the subjects of social economy stand out, the strong ability to include people, the pursuit of autonomy, empowerment and citizenship will manifest in these subjects to participate in decisions within and outside the enterprise. The commitment to build new working relationships, to fight for public policies that serve the industry and the willingness of the Movement to occupy and move in public spaces. Another possibility is the strong impact of these enterprises in local suatainable economic development and economic democratization process